The Acute Treatment of Migraine Attack in Adults and American Headache Society Evidence Assessment of Migraine Pharmacotherapies - Dikmen, Pinar Yalinay (TURKISH NEUROLOGICAL SOC, 2016)
Migraine is a common, the primary debilitating and recurring headache disorder. The main purpose migraine acute pharmacology is to reduce the impact and disability caused by the attack of migraine. This review primarily reminds clinical pearls in acute treatment of migraine and also summarizes the American Headache Society Evidence Assessment of Migraine Pharmacotherapies that published last year.
Keywords: Migraine; attack treatment; migraine pharmacotherapies